Pelaksanaan Uji Sondir Untuk Analisis Kondisi Tanah Di Gereja Bnkp Hosiana Dalam Rangka Penguatan Perencanaan Pembangunan Gedung Gereja - Dermawan Zebua; Bimawijaya Laia; Hamedoni Harita; Jun Fajar Krisman Giawa; Kevin Berkat Mendrofa (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2025)
This study aims to analyze the soil conditions at the construction site of the BNKP Hosiana Church by conducting cone penetration tests (CPT) as a basis for designing a safe and efficient foundation system. The CPT was performed to obtain cone resistance (qc), sleeve friction (fs), and friction ratio (Rf) across various soil depths. The results indicate the presence of three main soil layers: a soft clay layer at depths of 0–2 meters with low bearing capacity, a silt or stiff clay layer at 2–6 meters with moderate bearing capacity, and a dense sand or hard layer below 6 meters characterized by high bearing capacity. Analysis based on the Robertson approach suggests that shallow foundations are not recommended due to the weak surface soil conditions. Deep foundations, such as driven piles or bored piles, are considered the most suitable option to reach the competent hard layer capable of supporting the structural load effectively. Therefore, the cone penetration test proves to be an essential tool for strengthening the planning of the BNKP Hosiana Church building project, particularly in ensuring the long-term safety and structural stability of the facility.